Brecha digital y estilos de enseñanza en docentes de las instituciones públicas de nivel inicial en Caballo Cocha provincia de Ramón Castilla 2022 - Campoverde Soria, Erika Karen (2023)
The following question was formulated in this research as a general problem: What is the relationship between the digital divide and teaching styles in teachers of the initial level Public Institutions in Caballo Cocha Ramón Castilla Province 2022? and as a general objective: Relate the digital gap and teaching styles in teachers of the initial level Public Institutions in Caballo Cocha Province of Ramón Castilla 2022. As a methodology, the type of relational research was applied, through a bivariate, field and cross-sectional design. 44 initial level teachers were the population and sample, duly validated questionnaires were applied to them through the survey technique. The research concludes that there is a statistically significant relationship between the digital gap variable and the open and functional teaching styles in teachers (rs=0.326*; Sig. <0.05; rs=0.331*; Sig. <0.05), but there is no relationship statistically significant with the structured and socio-functional teaching styles (rs=0.063°; Sig. > 0.05; rs=0.245°; Sig. > 0.05).